1981
DOI: 10.2337/diab.30.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Diabetic Nephropathy by Diet Control in the db/db Mouse

Abstract: Diabetes in the C57BL/KsJ(db/db) mouse is initially expressed as hyperinsulinemia, followed by hyperphagia, progressive obesity, and widespread pathologic abnormalities. This study was designed to evaluate the effects of metabolic control on the natural history of the diabetic nephropathy. Beginning at 1 mo of age and continuing for 12 wk, diabetic mice were subjected to controlled dietary restriction, such that their weight was maintained similar to that of age-matched, nondiabetic heterozygotes. Diet-restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(43 citation statements)
references
References 0 publications
4
39
0
Order By: Relevance
“…After 10–20 weeks of sustained hyperglycemia, it exhibits significant renal pathology including glomerular mesangial expansion, accumulation of mesangial matrix encroaching the normal capillary network, overexpression of mRNAs encoding alpha 1 (IV) collagen and fibronectin, reduction in creatinine clearance, and a rise in serum creatinine concentration [6, 7, 8, 9, 10, 11]. These renal structural and functional abnormalities resemble, in their evolution and nature, those observed in human diabetes, rendering the db/db mouse a potentially useful model for study of pathogenetic influences and intervention strategies in the nephropathy of type II diabetes [7, 8, 9, 11, 12, 13]. We have used the db/db mouse to show that increased circulating concentrations of glycated albumin play a major causative role in the genesis of diabetic kidney disease by demonstrating that the renal cell biology, histomorphometric and functional abnormalities observed in these animals are prevented when the influence of excess plasma glycated albumin is blocked by treatment with monoclonal antibodies that specifically react with albumin modified by Amadori glucose adducts [7, 8, 9, 14].…”
Section: Introductionmentioning
confidence: 99%
“…After 10–20 weeks of sustained hyperglycemia, it exhibits significant renal pathology including glomerular mesangial expansion, accumulation of mesangial matrix encroaching the normal capillary network, overexpression of mRNAs encoding alpha 1 (IV) collagen and fibronectin, reduction in creatinine clearance, and a rise in serum creatinine concentration [6, 7, 8, 9, 10, 11]. These renal structural and functional abnormalities resemble, in their evolution and nature, those observed in human diabetes, rendering the db/db mouse a potentially useful model for study of pathogenetic influences and intervention strategies in the nephropathy of type II diabetes [7, 8, 9, 11, 12, 13]. We have used the db/db mouse to show that increased circulating concentrations of glycated albumin play a major causative role in the genesis of diabetic kidney disease by demonstrating that the renal cell biology, histomorphometric and functional abnormalities observed in these animals are prevented when the influence of excess plasma glycated albumin is blocked by treatment with monoclonal antibodies that specifically react with albumin modified by Amadori glucose adducts [7, 8, 9, 14].…”
Section: Introductionmentioning
confidence: 99%
“…The initial detailed studies by Like et al [27] over 30 years ago, followed by studies by Lee and Bressler [22] 10 years later, demonstrated that before the onset of hyperglycemia in these diabetic mice there was no difference in various glomerular parameters when compared with their nondiabetic littermates. After 5 to 6 months of age, diabetic mice have larger glomeruli and an increase in mesangial matrix when assessed by light microscopy.…”
Section: Glomerular Changes In the Db/db Mousementioning
confidence: 98%
“…Natural history of diabetes and obesity in the db/db mouse All db/db mice are obese after the age of 4 weeks [22]. Hyperinsulinemia can be seen after 10 days of age, with a 50% rise in body weight noted after 2 months of age.…”
Section: C57blks/j Versus C57bl/6j Background In the Db/db Mousementioning
confidence: 98%
See 1 more Smart Citation
“…We have identified a heteroaryl acid, designated EXO-226, that binds to glycatable lysine residues in albumin and thereby impedes the condensation of free glucose with ε-amino groups in the protein, and that reduces glycated albumin concentrations in human subjects [23, 24]. On the basis of these findings, we evaluated whether a treatment regimen of EXO-226 that significantly lowers plasma glycated albumin concentrations can beneficially influence abnormalities in renal structure and function that are known to occur in the db/db mouse model of type 2 diabetes [7, 8, 9, 25, 26, 27]. …”
Section: Introductionmentioning
confidence: 99%